PROGNOSTIC FACTORS FOR RESECTABLE COMMON BILE DUCT CANCER - A. Yu. Syskova; I. S. Stilidi; A. N. Polyakov (Исследования и практика в медицине, 2019)
Common bile duct cancer is a rare malignant disease with a poor prognosis. Five-year overall survival is 18-48%, and more than half of the patients relapse within five years.Metastases in the regional lymph nodes and the presence of tumor cells in the margin of the resection are independent factors of a negative prognosis and are associated with a high risk of recurrence.The clinical significance of other prognostic factors, such as renal invasion, low degree of differentiation, tumor size, pancreatic invasion and the need for resection of adjacent organs, require further study.